Ensino e aprendizagem do Oboé nos cursos de formação superior em Música da UFPB - Azevedo, Alisson Braulio de Aguiar (2020)
The present research, of a qualitative character, sought to answer the following problem: What are the strategies of Oboe students in higher education courses in music (bachelor's and undergraduate) at UFPB for learning the instrument? Bearing in mind that, in Brazil, researchaimed at understanding the teaching and learning of musical instruments is still moving towards becoming a consistent theme and with a wide range of materials in its framework. For that, it was necessary to use a bibliographic research that would guide thinking in an interdisciplinary way, where references from the field of music education, psychology and ergonomics were present in this referential scope. The methodological procedures were based on the elaboration of an interview with a semi-structured questionnaire, and with six aspects of analysis to understand the theme, listed as follows: Classes; Reeds; Orchestral excerpts; Interpretive Recitals / Practices; Master Classes; Pandemic (aiming at the need to understand how the class is being offered in this period of social distance). The analysis and interpretation of the data contributed to the understanding of the present theme, and, in this way, the intersection of information and references offered us to apply the objectives that were intended for this research. Based on the analyzes of the PPCs, it was possible to glimpse the contents inherent to the training of music professionals that UFPB foresees for society, and, from this conception, to link a point of view to understand the oboists' training disciplines. It appears that there is total immersion, on the part of the student, in the deliberate and planned approaches by the teacher, and, consequently, there is a search for practices that can bring autonomy to the deliberate study and those aspects inherent to the transversality of musical knowledge. In this way, we can find, according to the commentary of this institution, proposals that aim at the construction and the contribution of the student's self-analysis around his performance perspectives.